KEWENANGAN CAMAT DALAM PEMBERDAYAAN PEMERINTAH NAGARI DI KECAMATAN SULIKI KABUPATEN LIMA PULUH KOTA - Edwar, Ricky; Rosadi, Otong (Universitas Ekasakti, 2021)
Law Number 23 of 2014 concerning Regional Government mandates the District Government to provide guidance and empowerment to the Village / Nagari Government through the Regional Apparatus / Camat organization. Article 226 paragraph (1) of Law Number 23 of 2014 concerning Regional Government states that in addition to carrying out the tasks referred to in article 25 paragraph (1) the Camat receives the delegation of part of the Regent / Mayor's authority to carry out part of the government affairs which fall under the authority of the Regency / City. Based on the background of the above thought, the problems discussed are, first, how is the implementation of the Camat's authority in empowering the Nagari government in Suliki District, Lima Puluh Kota Regency? and second, what are the obstacles faced in empowering Nagari government in Suliki District, Lima Puluh Kota district? This research is a descriptive analytical study, with the normative juridical approach as the main approach and the empirical juridical as the support for the main approach. The data collected are secondary data and primary data. Data collection techniques with field studies through interviews for primary data and literature study for secondary data. The data obtained were analyzed qualitatively and presented in descriptive analytical form, which only described how the Camat's authority was exercised, the obstacles faced and the efforts made to overcome obstacles in the implementation of the Camat's authority in empowering the Nagari Government in Suliki District, Lima Puluh Kota Regency. Based on the results of research and discussion, it can be concluded that Law Number 23 of 2014 concerning Regional Government, Government Regulation Number 17 of 2018 concerning Districts and Regulation of the Regent of Fifty Cities Number 72 of 2016 concerning the Position of the Organizational Structure, Duties and Functions and Administration of the sub-districts has arranged in detail the duties and authorities of the Camat in empowering the Nagari government. However, the fact is that the guidance, empowerment and supervision of the nagari are mostly carried out by sectoral institutions / agencies. This, of course, will indirectly result in a reduction in the authority of the Camat in carrying out activities, especially those concerning Nagari governance. As a result, the control range is too far causing ineffective and inefficient implementation of tasks in the sub-district as well as in the nagari. The obstacles faced by the sub-district head in the process of empowering the village government are the limited and unclear authority which results in unallocated budgets to empower the village government and the lack of coordination between the District Government and the Nagari Government. The effort made by the sub-district head is to continue carrying out his duties in accordance with the Regulation of the Regent of Fifty Cities Number 72 of 2016 concerning 2016 concerning the Position of the Organizational Structure, Duties and Functions and Work Procedures of the sub-districts